2001
DOI: 10.1136/bmj.323.7320.1033
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal growth and risk of occlusive and haemorrhagic stroke in Swedish men and women born 1915-29: historical cohort study

Abstract: Evidence for an inverse association of impaired fetal growth with stroke is less securely established than that with coronary heart disease. Even less is known about the association of fetal growth with occlusive stroke and haemorrhagic stroke. Participants, methods, and resultsThe cohort comprises all 14 611 births in the Uppsala Academic Hospital between 1915 and 1929.1 Socioeconomic circumstances and neonatal characteristics, including gestational age (number of completed weeks since last menstrual period),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 4 publications
(4 reference statements)
3
35
0
Order By: Relevance
“…16 We divided stroke into 3 categories, thrombotic, hemorrhagic, and other, based on groupings in the international classification of disease that have been used in previous analyses. [5][6][7] The number of cases in our study was insufficient for examination of smaller diagnostic groupings, such as subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 We divided stroke into 3 categories, thrombotic, hemorrhagic, and other, based on groupings in the international classification of disease that have been used in previous analyses. [5][6][7] The number of cases in our study was insufficient for examination of smaller diagnostic groupings, such as subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] This association is independent of the length of gestation and therefore reflects slow fetal growth. Low body mass index at birth was also associated with later stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that each additional kilogram of birth weight was associated with a 11% decreased risk of stroke, with the exception of macrosomic infants [20]. In another cohort of women and men from Sweden, each kilogram increase in birth weight was associated with a 41% decreased risk of haemorrhagic stroke [21]. In the study by Singhal and Lucas, stroke risk generally rose with adult BMI and dropped with high birth weight, implicating rapid weight gain as a risk factor for stroke, as suggested by the 'growth acceleration' hypothesis [22].…”
Section: Discussionmentioning
confidence: 99%
“…This cohort has previously been used to investigate breast cancer incidence 11 as well as circulatory morbidity 12 and mortality 2 in relation to birth characteristics.…”
mentioning
confidence: 99%